Is bariatic surgery the cure for diabetes mellitus? - Nik Ritza Kosai Nik Mahmood (Penerbit UKM, 2013)
Obesity is a life-long, progressive, life-threatening, costly, genetically-related, multi-factorial disease of excess fat storage with multiple co-morbidities. Bariatric Surgery is currently the most effective therapy available for morbid obesity and can result in improvement or complete resolution of obesity related co-morbidities including diabetes mellitus.